A Case Study on Academic Innovations in Kerala Higher education - Chackochan J Njavallil AND Joby Joseph (IJRAR October, 2018)
An attempt was made to study the experience regarding the select academic innovations, to identify the problems faced and to draw insights based on the experience of the students and to suggest measures for improvement. It is clear that the respondents are generally satisfied with the overall conduct of Moodle examinations. They are mostly dissatisfied regarding the time in which the question bank was provided and with the existing academic calendar. The effectiveness of the academic innovations can be improved by addressing the main difficulties. The college can provide the question banks before. Most of the academic innovations implemented in the college have been effective, while a few need improvement.